Floral biology and pollination of Casearia grandiflora, Casearia javitensis and Lindackeria paludosa (Flacourtiaceae) in the region of Manaus, AM - Vásquez, Silvia Patricia Flores; Webber, Antonio Carlos (Revista Brasileira de Botanica, 2010)
Floral biology, pollination and reproductive system of Casearia grandiflora Cambess., C. javitensis Kunth and Lindackeria paludosa (Benth.) Gilg were studied on the Federal University of Amazonas campus, Manaus, Amazonas, Brazil (03°04'34" S, and 59°57'50" W), from November 2003 to December 2004. Observations of morphology, floral biology and floral visitors were made. The reproductive system and reproductive success was determined through field experimental pollinations. The flowers are hermaphrodites or staminated in Lindackeria paludosa and hermaphrodites in Casearia species, which emit a sweet scent during anthesis and has pollen of high fertility. Lindackeria paludosa and Casearia javitensis flowers open in the morning, whereas Casearia grandiflora flowers open at night. The main pollinators are flies of the Syrphidae family for the Casearia and bees of the Apidae and Halictidae families for L. paludosa. The results of the manual pollinations indicate that Casearia grandiflora and Lindackeria paludosa are auto-compatible species, in contrast to Caseria javitensis which is auto-incompatible. The species present a high reproductive potencial, but a low pre-emergent reproductive success.
Biologia floral e polinização de Casearia grandiflora, Casearia. javitensis e Lindackeria paludosa (Flacourtiaceae) na região de Manaus, AM
Keywords: Apidae; Apoidea; Casearia; Casearia Grandiflora; Casearia Javitensis; Flacourtiaceae; Halictidae; Lindackeria Paludosa; Pluchea Odorata Odorata; Syrphidae